2021
DOI: 10.1002/ep.13620
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the cathodic contribution of an electrooxidation pretreatment study on waste activated sludge disintegration

Abstract: In this study, the effect of the cathodic contribution in the performance of electrooxidation (EO) pretreatment of waste activated sludge (WAS) was investigated using different electrode pairs, namely titanium dioxide (TiO 2 )/TiO 2 , TiO 2 /TiO 2 coated Platine (Pt) and TiO 2 /TiO 2 coated ruthenium dioxide (RuO 2 ) and main operational parameters such as dosage of electrolyte solution (Na 2 SO 4 ), initial pH, applied current, and electrolysis time were optimized. Disintegration degree (DD) in terms of solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Furthermore, a study by Heng et al [19] showed a solid removal rate of 38% with Ti/RuO 2 electrodes considering the current density (6 mA/cm 2 ), electrolysis time (35 min) and sodium chloride (NaCl) electrolyte (1000 mg/L). Erkan et al [20] also reported a disintegration degree of 23.93% on pre-treated WAS, conducted at pH 10 with 3 A for 100 min using Ti/RuO 2 electrodes. Another research on EO pre-treatment of food waste using Ti/RuO 2 electrodes conducted by Liyanage and Babel [2] with operating conditions of 20 V for 40 min improved the sCOD solubilization by 40%.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, a study by Heng et al [19] showed a solid removal rate of 38% with Ti/RuO 2 electrodes considering the current density (6 mA/cm 2 ), electrolysis time (35 min) and sodium chloride (NaCl) electrolyte (1000 mg/L). Erkan et al [20] also reported a disintegration degree of 23.93% on pre-treated WAS, conducted at pH 10 with 3 A for 100 min using Ti/RuO 2 electrodes. Another research on EO pre-treatment of food waste using Ti/RuO 2 electrodes conducted by Liyanage and Babel [2] with operating conditions of 20 V for 40 min improved the sCOD solubilization by 40%.…”
Section: Introductionmentioning
confidence: 94%
“…An innovative pre-treatment-electrochemical oxidation (EO), a form of advanced oxidation process, has been showing its positive traits as a pre-treatment, to improve the biodegradability of waste activated sludge (WAS) [18][19][20][21]. EO is a clean technology that involves electrons by generating strong oxidizing agents in breaking down the EPS protecting layer of organic matter, which subsequently helps in dewatering and degrading the organic matters into simpler forms to help with the subsequent AD process [3,10,22].…”
Section: Introductionmentioning
confidence: 99%